Framework for the audit process implementation on public buildings - Md Ariffin, Khadijah (2015)
Audit of public buildings (PBs) is a relatively new phenomenon in the construction industry in Malaysia. Until 2006, there was no such audit conducted on PBs in Malaysia. In 2007, the government, through the Public Works Department (PWD) introduced audit on all buildings owned by the federal government. However, no formal studies have been conducted to explore the processes involved in the audit performed by PWD. An exploratory study was conducted to identify the processes involved in the audit of PBs by PWD. The exploratory study conducted concluded that full phase of audit was not implemented by PWD. Research findings from the exploratory study identified that PWD is the only agency in Malaysia which conducts technical audit on PBs. The finding has stimulated this study to refine research questions; justify a single and holistic case study as a research approach and identify the stakeholders involved in the audit process. A framework for identifying the stakeholders involved and their tasks and expectations which lead to the requirements needed to implement full phase of audit is further developed and applied for the Batu Pahat District Health Clinic (The Clinic Building). Hence, the study aims to investigate other requirements that are needed for full phase of audit being implemented for the Clinic Building by PWD. This study explores the key stakeholders involved, and their level of involvement in the audit process; barriers for full engagement of the audit process; and the stakeholders’ expectations for the audit process that lead to the barriers and issues that arises from the audit process by PWD. This study applies qualitative research methodology with a case study design, and adopts rigorous data collection and analysis. Interviews and focus group were used as the main data collection method in obtaining the right data for the study. The data were then analysed using NVivo 2 as a tool. Research findings from the case study lead to the introduction of a framework for implementing full phase of audit on PBs for PWD. This leads to the identification of additional requirements needed for the full phase of audit on PBs by PWD. It generates new knowledge on the requirements of the full phase of an audit process on PBs in Malaysia.